The reality of remote extended reality research: Practical case studies and taxonomy - Kroma, Assem; Grinyer, Kristen; Scavarelli, Anthony; Samimi, Elaheh; Kyian, Stanislav; Teather, Robert J. (Frontiers in Computer Science, 2022)
Remote user studies – those where the experimenter and participant are not physically located together – offer challenges and opportunities in HCI research in general, and extended reality (XR) research specifically. The COVID-19 pandemic has forced this form of research to overcome a long period of unprecedented circumstances. However, this experience has produced a lot of lessons learned that should be shared. We propose guidelines based on findings from a set of six remote virtual reality studies, by analyzing participants’ and researchers’ feedback. These studies ranged from one-session types to longitudinal ones and spanned a variety of subjects such as cybersickness, selection tasks, and visual search. In this paper, we offer a big-picture summary of how we conducted these studies, our research design considerations, our findings in these case studies, and what worked well and what did not in different scenarios. Additionally, we propose a taxonomy for devising such studies in a systematic and easy-to-follow manner. We argue that the XR community, should move from theoretical proposals and thought pieces to testing and sharing practical data-informed proposals and guidelines.